2021
DOI: 10.1177/10775595211004783
|View full text |Cite
|
Sign up to set email alerts
|

Public Opinion About Adverse Childhood Experiences: Social Stigma, Attribution of Blame, and Government Intervention

Abstract: Adverse childhood experiences (ACEs) are receiving increasing attention in academic, policy, and media discourses. However, no public opinion research has focused on ACEs. We conducted a nationally representative survey of U.S. adults to address this knowledge gap. A web-based survey was conducted using the Ipsos KnowledgePanel ( N = 503, completion rate = 60.5%) in fall 2019. We found that inter-personal stigma and parental blame related to ACEs were prevalent, with 25.0% of respondents unwilling to have a pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…Nearly one third of ACE articles identified having a primary caregiver with a mental health or substance use problem as a cause of ACEs. Although this is consistent with how ACEs are operationalized and measured, this message suggests that caregivers with these problems increase their children’s risk of negative outcomes later in life (Macvarish & Lee, 2019; Purtle et al, 2021). This could potentially amplify negative attitudes toward people with mental health and substance use problems a population that is already highly stigmatized (Barry et al, 2014; Stringer & Baker, 2018).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Nearly one third of ACE articles identified having a primary caregiver with a mental health or substance use problem as a cause of ACEs. Although this is consistent with how ACEs are operationalized and measured, this message suggests that caregivers with these problems increase their children’s risk of negative outcomes later in life (Macvarish & Lee, 2019; Purtle et al, 2021). This could potentially amplify negative attitudes toward people with mental health and substance use problems a population that is already highly stigmatized (Barry et al, 2014; Stringer & Baker, 2018).…”
Section: Discussionsupporting
confidence: 57%
“…The identification of primary caregivers as causes of ACEs in newspaper articles could also contribute to parental blame. A 2019 public opinion survey, which defined ACEs and summarized evidence about ACEs as risk factors for negative outcomes in adulthood, found that 65% of respondents believed that parents were “very much to blame” for the consequences of ACEs (Purtle et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Much violence against children remains largely hidden and unreported because of fear and stigma and the societal acceptance of this type of violence (Pinheiro, 2006;Norman et al, 2012). Especially in Chinese undergraduates, Confucianism values and traditional cultures are rooted in thoughts (Ng, 1997), which may contribute to stigma formation, F., more shame toward ACEs (Mukolo et al, 2010;Purtle et al, 2021). Regarding BCEs, 65.7% of undergraduates reported more than 8 BCEs.…”
Section: Discussionmentioning
confidence: 99%
“…The present findings provide support for the distinction between the diverging processes of identification and disidentification (Becker & Tausch, 2014; Elsbach, 1999; Ikegami & Ishida, 2007; Verkuyten & Yildiz, 2007). The results demonstrated that indeed the stigma associated with experiences of childhood adversity (Purtle et al, 2022; Tasheuras, 2019) was linked to amplified responses to trauma, that is, heightened levels of dissociation (Schneider et al, 2018; Verelst et al, 2014) through disidentification rather than identification processes. This finding supports previous research that shows how, on a personal level, survivors cope with their trauma through dissociation as a way to protect themselves (Choi et al, 2017).…”
Section: Discussionmentioning
confidence: 96%